The MET Oncogene: Thirty Years of Insights into Molecular Mechanisms Driving Malignancy - Tiziana Crepaldi; Simona Gallo; Paolo Maria Comoglio (MDPI AG, 2024)
The discovery and subsequent research on the MET oncogene's role in cancer onset and progression have illuminated crucial insights into the molecular mechanisms driving malignancy. The identification of MET as the hepatocyte growth factor (HGF) receptor has paved the path for characterizing the MET tyrosine kinase activation mechanism and its downstream signaling cascade. Over the past thirty years, research has established the importance of HGF/MET signaling in normal cellular processes, such as cell dissociation, migration, proliferation, and cell survival. Notably, genetic alterations that lead to the continuous activation of MET, known as constitutive activation, have been identified as oncogenic drivers in various cancers. The genetic lesions affecting MET, such as exon skipping, gene amplification, and gene rearrangements, provide valuable targets for therapeutic intervention. Moreover, the implications of MET as a resistance mechanism to targeted therapies emphasize the need for combination treatments that include MET inhibitors. The intriguing "flare effect" phenomenon, wherein MET inhibition can lead to post-treatment increases in cancer cell proliferation, underscores the dynamic nature of cancer therapeutics. In human tumors, increased protein expression often occurs without gene amplification. Various mechanisms may cause an overexpression: transcriptional upregulation induced by other oncogenes; environmental factors (such as hypoxia or radiation); or substances produced by the reactive stroma, such as inflammatory cytokines, pro-angiogenic factors, and even HGF itself. In conclusion, the journey to understanding MET's involvement in cancer onset and progression over the past three decades has not only deepened our knowledge, but has also paved the way for innovative therapeutic strategies. Selective pharmacological inactivation of MET stands as a promising avenue for achieving cancer remission, particularly in cases where MET alterations are the primary drivers of malignancy.